If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2z + -7)(-8 + 5) = 0 Reorder the terms: (-7 + -2z)(-8 + 5) = 0 Combine like terms: -8 + 5 = -3 (-7 + -2z)(-3) = 0 Reorder the terms for easier multiplication: -3(-7 + -2z) = 0 (-7 * -3 + -2z * -3) = 0 (21 + 6z) = 0 Solving 21 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 6z = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 6z = 0 + -21 6z = 0 + -21 Combine like terms: 0 + -21 = -21 6z = -21 Divide each side by '6'. z = -3.5 Simplifying z = -3.5
| X-14=-36 | | 25y-36y^2= | | 27x-6+15x^2= | | (x-7)(-4x+5)=0 | | -28-4v=-2v+8(v-6) | | 7x-17+3x+117=180 | | (w-7)(-6w+5)=0 | | 3x^3-24x^2-3x+24=0 | | 5(6x+3)=10(3x-4) | | 35x^2y+14xy-21xy^2=0 | | (s+1)(9s+1)=0 | | 56-6x=2x-48 | | (n-1)(n-5)=0 | | 2u(u-4)=0 | | 2(7x-8)+5=14x-11 | | (16-8)3+22/11= | | (5d-7)(7d+2)=0 | | d+12=20-3d | | x-4.3=23 | | p(p+7)=0 | | -24s+-53=39+-s | | (t-8)(t-5)=0 | | 7x+6-3x=13x+17 | | x-4.3=19 | | -1-2=3y | | -54=-4(3n+1)+2n | | (7v+3)(7v+9)=0 | | y=-2x^5+16x^4+66x^3 | | z^2-5z+7+z=0 | | 15z^2+7z-16=0 | | g(9g+7)=0 | | 8x+8=38 |